2013
DOI: 10.1177/0010414012472466
|View full text |Cite
|
Sign up to set email alerts
|

The Revolutionary Power of Peripheral Agencies

Abstract: This article challenges the long-standing emphasis in the developmental state literature on the powerful pilot agency as an essential component of industrialization. Although a pilot agency may be able to facilitate growth in mature industries, we argue that policy makers seeking to promote rapid innovationbased competition must instead rely on continuous, radical policy innovation. We argue that this kind of experimentation is more likely to occur at the periphery of the public sector, in agencies with few ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…In this configuration some redundancy between government functions can be beneficial since it increases the chances of new ideas finding a space within the public sector. Further insights into achieving both coordination and policy innovation come from Breznitz and Ornston's (2013) case studies in Israel and Finland. They found that agencies with limited power and resources, yet a high degree of freedom and flexibility, produced new policy models that were picked up by other sections of government at critical moments.…”
Section: Comprehensivenessmentioning
confidence: 99%
“…In this configuration some redundancy between government functions can be beneficial since it increases the chances of new ideas finding a space within the public sector. Further insights into achieving both coordination and policy innovation come from Breznitz and Ornston's (2013) case studies in Israel and Finland. They found that agencies with limited power and resources, yet a high degree of freedom and flexibility, produced new policy models that were picked up by other sections of government at critical moments.…”
Section: Comprehensivenessmentioning
confidence: 99%
“…For instance, Israel's gross expenditure on R and D (GERD) in 2014 stood at 4.11 percent of GDP, more than twice the EU average of 2.03 percent. The country's vibrant entrepreneurial and high-technology scene (Avnimelech and Teubal 2006;Breznitz and Ornston 2013;Trajtenberg 2001;Wonglimpiyarat 2016) has attracted international attention. When compared to previous R and D framework programmes, the participation of entities from Israel in Horizon 2020 seems to increase (Garcia-Torres 2016, pp.…”
mentioning
confidence: 99%
“…Other policies implemented by the Office of the Chief Scientist (OCS) during the 1990s and early 2000s followed the same entrepreneurial-state logic as Yozma. Programmes started since the beginning of the 1990s include the Magnet programme for collaborative generic research, the technological incubators programme that is said to support the creation of about 70-80 new businesses annually, the Tnufa programme for start-up assistance in the pre-seed phase, the Nofar programme for applied biotechnology R and D, and the Heznek seed fund that matches private investments with public funds (Breznitz andOrnston 2013, p. 1235;Trajtenberg 2002;Wonglimpiyarat 2016, pp. 24-26).…”
mentioning
confidence: 99%
See 2 more Smart Citations